Epitomic Representation of Nepalese cultural Trauma in Narayan Wagle’s ‘Palpasa Café’ (शोधसुधा Shodh Sudha, 2025)
This research paper explores the theme of cultural trauma represented by Narayan Wagle’s Palpasa Café. The protagonist, Drishya’s trauma stands for the then Nepalese trauma due to Maoist insurgency. In order to justify how his traumatic experience speaks for the whole Nepalese citizens’ misery, this article prominently applies the traumatic theories of Jeffery et al., Cathy Caruth, and LaCapra. The central objective is to evoke a shared sense of suffering between the hero and the Nepalese people, as his anguish reflects that of a member intrinsically bound to the cultural collective. Drishya’s melancholies due to war and its consequences vehemently shout for the loss of loved ones of those millions of Nepalese. Moving from Drishya’s psychological trauma to communal one bitterly stands for each individual and his personal history mirrors the lived realities of the broader community. He is the witness and witnesses ghastly bloody deaths that significantly evokes the aghast images the public profoundly endured at the time. The Nepalese relate Drishya on an intensely personal level, a profound testament to the lived reality of cultural trauma.